Empowering African Citizen for Sustainable Environmental Governance: Envisioning a New Africa - Sunday, Odediran Bukola; Muhammed, Salisu Umar (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
The environmental challenges facing the African continent are of critical concern, with rapid urbanization, resource depletion, and climate change posing significant threats to its ecological integrity and socio-economic stability. This paper presents a strategy for resolving these problems by enabling citizens to participate in sustainable environmental governance. This suggested framework is based on a multifaceted approach that combines advocacy for public policy, community participation, education, and technological innovation. It underlines the part played by involving citizens in fostering environmental sustainability. The concept of a "New Africa" envisions a populace that is and empowered to actively engage in environmental policy and practice-related decision-making. The emphasis on inclusive and participatory government that results from this paradigm shift ensures that the various views and viewpoints of African communities are heard and valued. African countries will be well-positioned to pave the way for sustainable environmental governance by adopting this forward-thinking paradigm, ensuring the peaceful co-existence of nature and society. The bedrock of this transformative journey will be the empowerment of African citizens, promoting a continent where the environment flourishes and communities prosper side by side. This vision provides a roadmap for a strong and wealthy Africa that is prepared to take on the challenges of the 21st century.